SYNTACTIC AND SEMANTIC FEATURES OF PROVERBS WITH PHYTONYMIC COMPONENTS - Nekboyeva Rano Zokirovna (Bright Mind Publishing, 2025)
This study examines the syntactic and semantic characteristics of proverbs containing phytonymic components—terms related to plant names—in English and Uzbek languages. By analyzing the structural patterns and metaphorical meanings of these proverbs, the research highlights how cultural perceptions of plants influence linguistic expressions. The findings reveal both universal and language-specific features in the use of plant-related metaphors, contributing to a deeper understanding of the interplay between language, culture, and cognition.
Keywords: Proverbs, phytonyms, syntax, semantics, metaphor, English, Uzbek, cultural linguistics.